2023
DOI: 10.3390/solids4030010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of In-Situ Low Copper Alloying of 316L Using the Powder Bed Fusion Process

Abstract: This study investigated the allowability of materials in the laser powder melting process, with a focus on powder mixing as a means of adjusting the material composition quickly and cost-effectively. By mixing different powders, a desired alloy can be created during additive processing without the need to produce new powder, which can be expensive. However, one of the main challenges in this process is the segregation of powders, which can lead to non-homogeneous alloys. To address this challenge, the study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Wang et al [14] fabricated a low-stiffness porous AISI 316L-4.5Cu by selective laser with similar stiffness (3-20 GPa) with bone to prevent stress shielding. Foadian et al [24] investigated AISI316L with two amounts of copper content by the L-PBF technique. They found that component density decreased by the addition of 5% copper.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [14] fabricated a low-stiffness porous AISI 316L-4.5Cu by selective laser with similar stiffness (3-20 GPa) with bone to prevent stress shielding. Foadian et al [24] investigated AISI316L with two amounts of copper content by the L-PBF technique. They found that component density decreased by the addition of 5% copper.…”
Section: Introductionmentioning
confidence: 99%